A study of the immune response to human papillomavirus types causing cervical cancer - Marais, Dianne Jean (Division of Medical Microbiology, 2025)
This study constitutes the first reported assessment in Africa of the antibody responses to human papillomavirus (HPV) proteins and the association of these responses with cervical disease. Immunoglobulin G (IgG) antibodies to HPV antigens were measured by enzymelinked immunosorbent assay (ELISA) in the serum of children, female blood donors, and patients with cervical intraepithelial neoplasia (CIN). A significant association with CIN was found for IgG antibodies to an E2 peptide (E2-16, P = 0.039) and HPV-16 virus-like particles (VLP-16, P = 0.002). This association was found to be age-dependant in women with CIN, with a higher antibody seropositivity rate to E2-16 noted in women over 40 years and a lower antibody seropositivity rate to VLP-16 found in the older women. This implied that in women with CIN, VLP-16 antibodies were markers of CIN in younger women and E2-16 antibodies markers of CIN in older women. A high antibody seroprevalence rate was noted in the children's sera to E2-16 (44.5%), with a decreased seroprevalence in older children. The assessment of seroresponses to VLPs ofHPV types 16, 18, 31, 33 and 45 in the women with cervical cancer (CaCx) as well as women with CIN, blood donors, San people and children is the first study of antibody responses to 5 oncogenic HPV VLP types. The prevalence rate to the 5 HPV VLP types was lowest amongst the children but 27.3% of Cape Town children and 22.6% Df the San children were seropositive to at least one VLP type, as were 58% of all adult women tested. The San adults displayed high seroprevalence rates to · VLP-18 and VLP-45, corroborating other evidence of the high prevalence rates ofHPV-18 and HPV-45 in parts of Africa. The antibody prevalence rates among the CIN patients' sera were elevated above that of blood donors, for all VLP types. VLP antibody prevalence rates in the CaCx patient sera were higher than prevalence rates of the CIN patients for all VLP types, with the exception of antibodies to VLP-16. Association with disease was found for IgG antibodies to VLP-16 and VLP-45 in women with CIN, compared with blood donor controls. This is the first report of an association of antibodies to VLP-45 with cervical disease. Seroprevalence to multiple VLP types was evident in all the groups studied, especially so in the women with cervical disease and was most common in older women with CaCx (55%). XVl The antibody responses appeared type-specific, but some cross reactivity was apparent, although not confirmed. Cross reactivity between antibodies to VLP-16 with antibodies to VLP-31, as well as antibodies to VLP-18 with VLP-45 antibodies appeared likely in some women. Anti-VLP-16 IgA antibody levels in oral fluid of women with CIN and CaCx were compared with those of normal healthy control individuals. Prevalence rates were 55.7% compared with 8% in the controls (P = 0.000002). A group of 26 women with CIN 2 or CIN 3 (CIN2/3) were examined for IgA and IgG antibodies to VLP-16 in serum and cervical mucus as well as oral fluid. The percentage of women with VLP-16 antibodies was highest for serum IgA (65.4%), with 61.5% of these women having detectable serum IgG and 42% and 38.5% IgA and IgG antibodies, respectively in cervical mucus. The serum IgG responses correlated best with the presence of HPV-16 deoxyribonucleic acid (DNA) at the cervix, with an 87.5% IgG antibody prevalence in women with CIN2/3 who were HPV-16 DNA positive. Commercial sex workers, at high risk of cervical disease, were examined for their HPV DNA presence and cervico-vaginal lavage and serum samples from these women were examined for anti-VLP-16 antibodies. Many of these women were infected with human immunodeficiency virus (HIV-positive) and others were not infected with HIV (HIV-negative). The HIV-positive women displayed a significant increase in the prevalence of HPV DNA (85%) compared with HIV-negative women (42%, P = 0.00001) and a significant increase in cervical anti-VLP-16 IgG antibodies (P = 0.002) and a significant decrease in anti-VLP-16 serum IgA (P = 0.012) . compared with HIV-negative women. This was the first published report of cervical antibodies to VLP-16 in HIV-positive women. A novel recombinant vaccinia virus (rVv)-HPV-16 Ll challenge model was developed to evaluate the efficacy of the cell mediated immune response following HPV-16 VLP immunisation in mice. Intra-peritoneal vaccination of BALB/c mice with HPV-16 VLPs afforded protection against viral challenge from rVv expressing HPV 16 Ll (VvLl1z:.-l6). Protection was demonstrated by a 4.6log10 reduction in Vv-LlR-16 ovarian titres in vaccinated BALB/c mice, compared with unvaccinated mice. The inability to infect laboratory animals xvu with HPV has in the past abrogated the testing of HPV vaccines in animal systems. Mice immunised intragastrically with VLP-16 were also protected from VvLlR-16 challenge. Three rBCG constructs expressing different lengths of the L 1 protein of HPV-16 were also tested for their ability to protect mice from VVLlR-16 challenge, and all induced >4log10 levels of protection. The mouse challenge model demonst_rated a quantitative measure of the protection induced by potential HPV vaccines.